(3bQGAI bGdhf hGdOhQjs - (3YKeGf Hf YeQ Hf CHj HcQ GdfGTQj, Yaja GdOjf , J (B848 (3g`s
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGaj fYeI hjcGaF eRjOg hbO GSJNQJ Gddg JYGdi hCedjJ gPg GdhQjbGJ aj ePgH bGdhf hGdOhQj s
(3BNQgG (B:s
(3Gddge CLYd GdbQBf MLI dfG, hdGJLYdg MLI YdjfG bGd eDdagG CcedJ JNQjLgG aj eOjfI RHjO JeJ hHGdNjQ YeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdfSNI HgG MhGTs
(3ocJHJ HYV GdYfhGfGJ HGdMeQIs
(3hGdfSNI ebGHdI Ohf JGQjN s
(3hQb CJe GdeDda JCdjagG SfI (B830(3g` s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdbQGAGJ hGdJLhjOs